Comparison of reservoir characteristics between continental shale from faulted basin and marine shale under high-over mature stage: Taking Shahezi Formation in Xujiaweizi faulted basin and Longmaxi Formation in Sichuan Basin as an example - ZHAO Renwen,XIAO Dianshi,LU Shuangfang,ZHOU Nengwu (Youqicang pingjia yu kaifa)
Gas bearing shale is widely developed in continental faulted basins in China. In the past, it was mainly studied as the gas source rock, and there was little research on its reservoir and influencing factors. It is urgent to carry out corresponding researches to clarify the main controlling factors of shale reservoir development in continental faulted basins. For the researches, the shale of Shahezi Formation in Xujiaweizi fault depression of Songliao Basin and Longmaxi Formation in Sichuan Basin are selected, and the difference of reservoir characteristics between high over mature continental fault depression basin and marine gas shale is compared and studied by the experiments such as organic geochemistry, whole rock analysis, scanning electron microscope, low-temperature nitrogen adsorption and nuclear magnetic resonance. The research shows that the shale formation environment of Shahezi Formation is diverse, the organic matter type is mainly type Ⅲ, the clay mineral content is high, the cemented quartz is developed, the clay related pores and quartz intergranular pores are the main pore types, the specific surface area is small but the pore diameter is large, and the reservoir development is controlled by compaction, clay mineral transformation and coal seam development; Longmaxi Formation shale was formed in shelf environment. The type of organic matter is mainly type Ⅰ, with high abundance of organic matter and high content of biogenic quartz. Organic pores and clay related pores are the main pore types, and the type and maturity of organic matter mainly control the development of pores. On the whole, the shale reservoir development conditions of Shahezi Formation are slightly worse than those of Longmaxi Formation, but the plain swamp microfacies shale is developed close to the coal seam, the authigenic cemented quartz is developed, the proportion of Yimeng mixed layer is high, the reservoir has high organic matter abundance, good compressibility, large pore volume and specific surface area and good porosity development, which can be used as a potential favorable target for further evaluation and research.